Pharmacoeconomic Analysis of Type 2 Diabetes Mellitus Patients with the Application of PGA (Use of Antimicrobials) at Hospital X in East Java - Dewi, Nisvi; Indrawati, Ratna; Tahjoo, Anastina (International Journal of Nursing and Health Services (IJNHS), 2025)
Background: Type 2 Diabetes Mellitus (T2DM) leads to a reduced immune response and increased susceptibility to infections, necessitating the use of antibiotics. However, inappropriate and excessive use of antimicrobials in humans, animals, and plants can contribute to increased antimicrobial resistance. Objective: This research aims to provide an overview of the application of Antibiotic Management (PGA) in the use of reserve antibiotics for T2DM patients concerning pharmacoeconomics at X Hospital in East Java. Method: Method: The study employed an observational approach with an exploratory descriptive method. Data were collected retrospectively from a cohort of patients who received reserve class antibiotics. The effectiveness of these antibiotics was assessed based on clinical outcomes, including patient survival or death, using medical records from October 2021 to September 2022 and October 2022 to September 2023. Result: The result indicated that the application of PGA using reserve antibiotics in T2DM patients had a positive and significant impact on pharmacoeconomics. The Incremental Cost Effectiveness Ratio (ICER) for T2DM patients with infections who received reserve antibiotics decreased after PGA implementation. Conclusion: The study concludes that PGA application in T2DM patients with infections yielded positive results, including a reduction in ICER, indicating improved cost-effectiveness and clinical outcomes. Recommendation: Proper and controlled use of reserve antibiotics through PGA can help mitigate antimicrobial resistance, a critical global health issue